Zinc stearate from galvanizing waste materials and its use as thermal stabilizer in PVC industries (Bangladesh Journal of Scientific and Industrial Research, 2016)
Galvanizing industries of Bangladesh produce profuse amount of environmentally hazardous solid waste materials like zinc dross which contains significant amount of valuable zinc and harmful heavy lead. Zinc was extracted as zinc chloride (ZnCl2) from zinc dross. Zinc stearate (ZnSt2) samples were prepared by precipitation method from stearic acid, sodium hydroxide and ZnCl2 by varying the amount of the reagents and product yield found within the range 96.06-99.18%. Characteristic peaks of ZnSt2 were investigated by Fourier Transform Infrared Spectroscopy (FTIR). Differential Scanning Calorimeter (DSC) onset curve assigned accurate melting point within the range 122.84-124.03°C. Surface morphology of ZnSt2 was observed by Scanning Electron Microscope (SEM) and products had semi-crystalline structure. Thermal stability of ZnSt2 was evaluated by Thermo-gravimetric Analyzer (TGA) that complied with literature. A combination of ZnSt2 and Calcium stearate (CaSt2) at 1:1 ratio was used as thermal stabilizer in the powder commercial grade PVC resin and performed better thermal stability. The dehydrochlorination temperature of PVC with mixed stearates was 344.67±1.04°C for 10% (w/w) loading whereas for PVC, PVC with 10% (w/w) ZnSt2 and PVC with 10% (w/w) CaSt2, it was 269.83±1.04°C, 317.33±1.26°C and 323.33±2.08°C respectively.Bangladesh J. Sci. Ind. Res. 51(4), 261-270, 2016